Fun School Movement Strategy Management in Realizing the Pancasila Student Profile at SDN Talang Layan - Widyaswari, Tri; Harapan, Edi; Rosani, Meilia (Universitas Pahlawan Tuanku Tambusai, 2025)
The Fun School Movement (GSM) and the Pancasila Student Profile are important because they encourage the creation of a humane, inclusive, and student-centered learning environment, as well as form the character of students who are faithful, independent, critically reasoning, mutual cooperation, creative, and globally diverse. This study is to describe how the strategic management of the Fun School Movement in realizing the Pancasila Student Profile. This study uses qualitative data, namely a qualitative descriptive method to obtain conclusions. This research is planned to be carried out from August 2024 to January 2025 at SDN Talang Layan related to the implementation of the strategic management of the Fun School Movement in realizing the Pancasila Student Profile. With data collection techniques through observation, interviews, documentation. The result of the study is that strategic management has an important role in the success of the Fun School Movement (GSM) at SDN Talang Layan. Through careful planning, structured implementation, and continuous evaluation, GSM can be an effective means of realizing the Pancasila Student Profile.